Impact of Pre-planting Inoculation with Phosphorus-solubilizing Bacteria on Potato Tuber Quality during Storage - Tainá Ferreira da Rocha; Fernando Angelo Piotto; Maria Carolina Quecine; Carlos Alberto Quiloango-Chimarro; Jéfferson de Oliveira Costa; Ralph Bonandi Barreiros; Marcos Fabián Sanabria Franco; Ricardo Alfredo Kluge (Potato Research, 2026)

Standardising research on marine biological carbon pathways required to estimate sequestration at Polar and sub-Polar latitudes - Simon A. Morley; David K.A. Barnes; Camila Neder; Ricardo Sahade; Chester J. Sands; Carla M. de Aranzamendi; Kaja Balazy; Piotr Balazy; Facundo Barrera; Narissa Bax; Sofia Becerra; Lucia Bergagna; et al. (Earth-Science Reviews, 2026)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

Mechanisms of Mucor sp. CM3 isolated from the aquatic macrophyte Eichhornia crassipes (Mart.) Solms to increase cadmium bioremediation - Tiago Tognolli de Almeida; Bruno Augusto Prohmann Tschoeke; Maria Carolina Quecine; Tiago Tezzoto; Salete Aparecida Gaziola; Ricardo Antunes Azevedo; Fernando Angelo Piotto; Ravely Casarotti Orlandelli; Manuella Nóbrega Dourado; João Lucio Azevedo (Environmental Science and Pollution Research, 2023)

The auxin-producing Bacillus thuringiensis RZ2MS9 promotes the growth and modifies the root architecture of tomato (Solanum lycopersicum cv. Micro-Tom) - Bruna Durante Batista; Manuella Nóbrega Dourado; Everthon Fernandes Figueredo; Renata Ockner Hortencio; João Paulo Rodrigues Marques; Fernando Angelo Piotto; Maria Letícia Bonatelli; Matthew L. Settles; João Lucio Azevedo; Maria Carolina Quecine (Archives of Microbiology, 2021)

Understanding Conformational Dynamics of Complex Lipid Mixtures Relevant to Biology - Ran Friedman; Syma Khalid; Camilo Aponte-Santamaría; Elena Arutyunova; Marlon Becker; Kevin J. Boyd; Mikkel Christensen; João T. S. Coimbra; Simona Concilio; Csaba Daday; Floris J. van Eerden; Pedro A. Fernandes; et al. (The Journal of Membrane Biology, 2018)

Cadmium exposure triggers genotype-dependent changes in seed vigor and germination of tomato offspring - Marcia Eugenia Amaral Carvalho; Fernando Angelo Piotto; Marina Lima Nogueira; Francisco Guilhien Gomes-Junior; Helena Maria Carmignani Pescarin Chamma; Daniel Pizzaia; Ricardo Antunes Azevedo (Protoplasma, 2018)